2014
DOI: 10.1353/hsj.2014.0009
|View full text |Cite
|
Sign up to set email alerts
|

Community-based Service-learning as a Context for Youth Autonomy, Competence, and Relatedness

Abstract: Framed by self-determination and identity development theories, this study examined the process through which participating in a community-based service-learning project supported high school students’ feelings of autonomy, competence and relatedness, and how these feelings were related to students’ intentions for doing more service in the future. The goals were to understand 1) the task and time related variations in students’ reports of autonomy, competence and relatedness, and 2) whether these task and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The self‐determination theory suggests that if volunteering activities support self‐determination, students are likely to internalize values associated with service to such an extent that it becomes a commitment to continuing service in the future (Deci et al 1994). Based on self‐determination theory, students who are given choices regarding where and how they will participate in volunteering activities and who are able to complete tasks they are good at, while connecting with others, are likely to perceive value from volunteering as a result of their needs for autonomy, competence, and relatedness being met (Kacker‐Cam and Schmidt 2014).…”
Section: Psm and High School Educationmentioning
confidence: 99%
“…The self‐determination theory suggests that if volunteering activities support self‐determination, students are likely to internalize values associated with service to such an extent that it becomes a commitment to continuing service in the future (Deci et al 1994). Based on self‐determination theory, students who are given choices regarding where and how they will participate in volunteering activities and who are able to complete tasks they are good at, while connecting with others, are likely to perceive value from volunteering as a result of their needs for autonomy, competence, and relatedness being met (Kacker‐Cam and Schmidt 2014).…”
Section: Psm and High School Educationmentioning
confidence: 99%
“…FFA sponsored civic engagement activities can occur in a variety of ways, including activities such as providing food to those unable to feed themselves, repairing or constructing community structures, or developing a community garden to educate the community on food production (National FFA Organization, 2017). Research indicates that short-term intensive community-based service learning projects support the competence, autonomy, and relatedness of the youth participants and also increases the likelihood of future participation in service projects (Kackar-Cam & Schmidt, 2014). FFA specific civic engagement activities potentially enhance agriculture students' sense of civic responsibility (Brandell & Hinck, 2005;Furco et al, 2016;Skinner & Chapman, 1999).…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
“…In the same study, other findings by Kacker-Cam and Schmidt (2014) suggested that service to people in need can promote desirable outcomes for students, such as greater selfefficacy and social concern, however, time spent on service shows no direct relationship between the amount of time spent performing the service and desirable outcomes. The study also noted the amount of time was not necessarily a good predictor of future service participation (KackerCam & Schmidt, 2014).…”
Section: Students' Perceptionsmentioning
confidence: 58%
“…The authors' findings also revealed that short-term intensive community service provided the best opportunity for the development of student autonomy, competence, and relatedness, all of which can aid in adolescent development, and promote self-determination and identity (Kacker-Cam & Schmidt, 2014). The findings on the volume of time spent performing community service is significant to the problem of practice, as community service in the school is sustained over a significant period of time, similar to the findings by Schmidt, Shumow, and Kacker (2007).…”
Section: Students' Perceptionsmentioning
confidence: 88%
See 1 more Smart Citation